20.2 HUMAN-INDUCED PLURIPOTENT STEM CELL MODELS OF AUTISM-ASSOCIATED MUTATIONS - Gupta, Abha R. (Journal of the American Academy of Child and Adolescent Psychiatry, 2016)
Objectives: The goal of this research is to generate cellular models of ASDs to elucidate its pathophysiology. Specifically, we study human-induced pluripotent stem cells (iPSCs) and subsequently derived neural progenitor cells (NPCs) and neural cells, which are stably knocked down for genes strongly associated with ASDs such as the chromatin modifier CHD8. Our goal is to compare these with cell lines that we have derived from patients with ASD with truncating CHD8 mutations. Methods: We have generated multiple iPSC clones from activated CD4+ T lymphocytes from a healthy male control subjects using Sendai virus to deliver reprogramming factors. After confirming pluripotency, we used CRISPR (clustered regularly interspaced short palindromic repeats) genome editing and homologous recombination to knock down the CHD8 gene. We then derived NPCs and a mixed population of neural cells from wild-type and CHD8 knockdown (KD) iPSCs. Results: RNAseq and Western blot analyses showed that CHD8 mRNA and protein were reduced by approximately 50 percent, which reflects the heterozygote state of all patients with ASD identified thus far with truncating CHD8 mutations. RNAseq data from three wild-type and three CHD8 KD iPSC colonies identified 632 genes that were expressed differentially between the two groups with q < 0.05. Functional annotation revealed that "cell adhesion" was among the most enriched terms for the down-regulated genes. Preliminary phenotyping has shown that, when plated at the same concentration, CHD8 KD iPSCs form a greater number of colonies than wild-type iPSCs. In addition, CHD8 KD NPCs do not form the typical polarized rosettes formed by wild-type NPCs in culture, perhaps because of disturbances in cell adhesion. Conclusions: Human iPSC modeling is providing insight into how truncating mutations in CHD8, a gene that is strongly associated with ASD, cause cellular derangements and possibly contribute to the pathophysiology of ASD. We plan to apply this approach to the investigation of additional ASD-associated genes to identify common biological mechanisms involving these genes.